Legal Aspects of the Social Regulator of Contractual Relations in Labor Law of Ukraine - T. P. Golopуch; I. M. Golopуch (Law and Safety)
Legal aspects of the social regulator of contractual relations in labor law of Ukraine have been revealed. The concept of social partnership and social dialogue as a legal regulatory mechanism of collective relations has been studied. Legal regulation of labor conditions at different levels, through agreements, reflecting the will and interests of the parties to the agreement, has been analyzed.